Long Range Correlated Motions of TIM and their Possible Influence on Enzyme Function - McKinney, J. A.; Deng, Y. T.; George, D. K.; Richard, J.; Markelz, A. G. (Biophysical Journal, 2020)
The alpha-beta barrel structure of triosephosphate isomerase (TIM) is possibly the most common among enzymes. In the case of TIM, structural dynamics are known to be essential to function. In particular the stabilization of the binding pocket by a phosphodianion “handle” of the substrate and the closing of catalytic site loops 6 and 7 over the substrate. Loop 6 moves by as much as 7 Angstroms with binding. Recently a mutant survey for human TIM (hsTIM) found kcat can change significantly for a single mutation distant from the catalytic site. Crystallographic measurements find no structural change with the mutation, suggesting a dynamical mechanism for the allosteric effect. Here we use Stationary Sample Anisotropic Terahertz Microscopy (SSATM) to measure the long-range intramolecular vibrations and determine if specific vibrations couple the allosteric and catalytic sites. SSATM isolated protein long-range structural vibrations based on the dominant displacement direction [1-4]. We examine if specific vibrational bands are associate with loop 6 and loop 7 flexibility.
ISI Document Delivery No.: KK8YX Times Cited: 0 Cited Reference Count: 4 Cited References: Acbas G, 2014, NAT COMMUN, V5, DOI 10.1038/ncomms4076 Niessen K.A. M.Y., 2017, BIOPHYS J, DOI [10.1016/j.bpj.2016.12.049.3., DOI 10.1016/J.BPJ.2016.12.049.3] Niessen K, 2019, OPT EXPRESS, V27, P28036, DOI 10.1364/OE.27.028036 Niessen KA, 2019, NAT COMMUN, V10, DOI 10.1038/s41467-019-08926-3 McKinney, Jeffrey A. Deng, Yanting George, Deepu K. Richard, John Markelz, Andrea G. 64th Annual Meeting of the Biophysical-Society Feb 15-19, 2020 San Diego, CA Biophys Soc NSFNational Science Foundation (NSF) [DBI 1556359, MCB 1616529]; DOEUnited States Department of Energy (DOE) [DE-SC0016317]; NIH STTRUnited States Department of Health & Human ServicesNational Institutes of Health (NIH) - USA [R41 GM125486.1] This work is supported by NSF grants DBI 1556359 and MCB 1616529, DOE grant DE-SC0016317 and NIH STTR R41 GM125486.1. 1 Cell press Cambridge 1542-0086
Keywords: Biophysics